Identifying a brain network profile disrupting obsessive-compulsive symptoms - Rajajärvi, Eveliina (My University, 2025)
Background: Obsessive-compulsive disorder (OCD) is a prevalent and debilitating neuropsychiatric disorder characterized by obsessive thoughts and compulsive actions. Despite numerous attempts to determine the neural correlates of OCD, functional and structural imaging methods have not provided consistent results. Aberrant functioning of several neural circuits, such as the cortico-striato-thalamo-cortical (CSTC) circuit, default mode network (DMN), frontoparietal network (FPN) and salience network (SN), have been associated with the pathophysiology of OCD (Stein et al., 2019). Combined, this and the heterogeneous nature of symptoms may imply that the disorder is network-based. Thus, the aim of this study is to explore whether it is possible to identify a functional connectivity profile associated with lesion-induced changes in obsessive-compulsive (OC) symptoms. Methods: Clinical assessments and brain imaging data was collected from 200 post-stroke patients prospectively enrolled as part of an on-going study at Turku University Hospital (Finland) (Liesmäki et al., 2024). Subjects’ OC symptoms were assessed using a revised obsessive-compulsive inventory (OCI-R) at two timepoints – acutely following the stroke and again at a follow-up visit (~4 months post-stroke). To be included in this study, patients must have had completed OCI-R assessment at both baseline and follow-up visits. Lesion-induced disruption in symptoms was defined as change in subjects’ OCI-R scores between baseline and follow-up assessments. Lesion network mapping (LNM) was used to explore the possible relationship between lesion connectivity and disruption in OC symptoms in three groups: 1) all subjects, 2) subjects with at least five-point change in their OCI-R score, and 3) within each symptom subtype. Functional connectivity profiles were created for all subjects to determine the lesion’s voxel-wise connectivity to all other brain regions. Then the individual connectivity maps were used for creating a unified R-map showing the regions connected to the lesion locations associated with the disruption in OC symptoms. Results: A total of 139 subjects were included. Functional connectivity analysis showed that lesion connectivity to the left precentral gyrus and left middle occipital gyrus was significantly associated (positive correlation) with OC symptoms (Puncorr<0.01). Lesion connectivity to the right middle occipital gyrus was significantly associated (negative correlation) with OC symptoms (Puncorr<0.01). Further, when examining only subjects that had at least a five-point change on their OCI-R scores (n=44), lesion connectivity to the right precuneus, right middle cingulum and right middle occipital gyrus were significantly associated (negative correlation) with symptom scores. Additionally, exploratory analyses identified networks for washing, obsessing, hoarding and checking subtypes. Discussion: Results from this study aligned with previous meta-analyses on network-based pathophysiology of OCD (Geffen et al., 2022; Gürsel et al., 2018). Aberrant functional connectivity to regions encompassed in FPN and DMN, as in the profile identified in this study, are commonly reported finding in OCD. In addition, results from analyzing each symptom dimension separately supported the idea of distinct brain network profiles for OC symptom subtypes. Overall, findings support the notion that OC symptoms may have network-based neurobiology and provide further evidence that LNM may provide a beneficial approach linking lesion induced changes in symptoms to a functional brain network. The identified networks may aid in future development of more efficient interventions and treatment targets for OCD and its subtypes.
Keywords: obsessive-compulsive disorder, OCD, lesion network mapping, functional connectivity